Study on intutionistic fuzzy Hausdorff ( T2) bitopological spaces: theoretical insights (Journal of Bangladesh Academy of Sciences, 2024)
In this document paper, we offer the concepts of some notions of Hausdorff (T2 ) property in intuitionistic fuzzy bitopological spaces. We demonstrate that each of them notion satisfies good extension property. We also establish that these notions satisfy hereditary properties. We observe that all the concepts of intuitionistic fuzzy Hausdorff bitopological spaces are preserved under one-one, onto, fuzzy mappings.J. Bangladesh Acad. Sci. 48(1); 51-59: June 2024